Proteolytic Activity of Oenococcus oeni Enables the Increase in Antioxidant and Antihypertensive Activities from Wine - Raquel Apud, Gisselle; Gilda Stivala, Maria; Aredes Fernandez, Pedro; Jose Rodriguez Vaquero, Maria (Current Pharmaceutical Biotechnology, 2013)
Oenococcus oeni is a lactic acid bacterium involved in winemaking where it generally carries out the malolactic fermentation converting the wine's malic acid into lactic acid. In this work were used the strain m of Oenococcus oeni. The culture was inoculated at 108 Log CFU/mL in a synthetic wine medium (SW) supplemented with a fraction of high molecular weight constituted by proteins and polypeptides (FPP) obtained from Cabernet Sauvignon and Syrah wines from Colalao del Valle, Tucumán, Argentine. In presence of FPP, O. oeni maintains viability after 48 h incubation time and release an extracellular proteolytic activity. Therefore, a release peptides of 1.247 and 1.373 mg N/L at 48 h of incubation time was detected in SW supplemented with FPP from Cabernet Sauvignon and Syrah wines respectively. Concomitantly with the maximum peptide release, the “in vitro” biological activities were increased. The released peptides from Cabernet Sauvignon wine enables the increase in the ferric reducing antioxidant power (FRAP) capacity, the scavenging activity of 2,2-diphenyl-1-picrylhydrazyl radical (DPPH), and the inhibition of angiotensin I-converting enzyme (ACEI activity) in 392.8 μmol FeSO4/L, 9.7% and 63.9%, respectively. In presence of FPP of Syrah wine, the released peptides increases in 156.5 μmol FeSO4/L, 5.5% and 13.8% the FRAP, DPPH and ACEI activities, respectively. The utilization of Oenococcus oeni m to carry out the malolactic fermentation would contribute to enhance the beneficial biological activities of the final product and provide an additional value to regional wines.
Keywords: Antihypertensive activity